Optimising PCR detection of Ralstonia solanacearum and Pseudomonas savastanoi pv. savastanoi: Two models, two approaches - Bertolini, Edson; Caruso, Paola; Penyalver, Ramón; Olmos, Antonio; Quesada, Jose M.; Cambra, Mariano; López, María M. (2017)
Available protocols and primers for PCR detection of Ralstonia solanacearum on water samples and Pseudomonas savastanoi pv. savastanoi on asymptomatic olive trees have relatively low reliability because of sensitivity and specificity problems.